RESILIENSI DAN AGENSI PEREMPUAN DALAM PEMULIHAN KRISIS DI PROVINSI BENGKULU - Rahmat Effendi; Inayah Rohmaniyah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Women become decisive agents in building resilience and community recovery in times of crisis, as happened in Bengkulu Province. One of the serious crises that society has recently faced has occurred due to the Covid-19 pandemic. The crisis arose due to various factors and the pandemic further exacerbated the impact of the crisis, even after the pandemic. In Bengkulu Province, the declining condition of the community has contributed to the increase in the number of cases. Even so, various parties have taken the best steps to overcome the crisis with various approaches. This article reveals the mainstream gender issues in Bengkulu Province society, especially during the pandemic, and how women seek solutions. This research is based on a literature study using the descriptive-analytical method. The theoretical framework used is gender and agency theory to see emerging gender issues and women's agency in tackling the complexity of the crisis in Bengkulu Province. This study shows that women's agency is seen in the realm of discourse and real action in society and contributes to building women's resilience in facing times of crisis. Through various discussions, scientific activities, and socialization in the context of educating women, they show their agency and resilience. Women's agencies are also seen in the form of real action in the community. This study provides recommendations to various parties in Bengkulu Province that to resolve the current and future crises, it is necessary to involve women and men in an egalitarian manner by upholding equal rights and obligations.